The effect of liberalizing basic financial variables on economic ‎growth Standard analytical study of the case of Algeria (1999-2015)‎ - Bouziane , Dalila; Ramdani, Mohamed (Dirassat Journal Economic Issue, 2017)
After a certain time began many countries to shift from a planned economy to a free economy, these countries has been placing attention so much financial and banking sector, and precipitated him to the liberation and openness as a condition of the conditions imposed by the International Monetary Fund and the World Bank in the context of economic and financial reform program, there are many Studies that have tried to establish a causal positive relationship between financial liberalization and economic growth appears and then the development of the financial sector. In the practical side focused attention on essayed measuring the impact of financial liberalization on the different aspects of economic growth, we have adopted the use of standard formats proposed for this purpose. And through it we tried to get out of indicators that reflect the effectiveness of financial liberalization in the internal and external sides of the economic growth in the case study of Algeria for the period 1999-2015. We have reached through this study that financial liberalization pursued a policy in Algeria did not have a positive impact on the achieved economic growth, it has also been reached through this study that some financial liberalization indicators and in spite of its importance in the economy, but it has no effect on growth rates economic.